2018
DOI: 10.2337/db17-1395
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Transcriptional Targets of Leptin Reveals a Role for Atf3 in Leptin Action

Abstract: Leptin acts via its receptor (LepRb) to modulate gene expression in hypothalamic LepRb-expressing neurons, thereby controlling energy balance and glucose homeostasis. Despite the importance of the control of gene expression in hypothalamic LepRb neurons for leptin action, the transcriptional targets of LepRb signaling have remained undefined because LepRb cells contribute a small fraction to the aggregate transcriptome of the brain regions in which they reside. We thus employed translating ribosome affinity pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 55 publications
0
43
0
Order By: Relevance
“…Of those, 562 DEGs were identified between Lep ob and WT mice ( Figure 1 C), of which 450 (80%) were upregulated and 112 (20%) were downregulated in Lep ob mice ( Figure S1 C and Table S1 ). Well-described leptin-regulated and/or energy balance-associated genes were detected: e.g., Agrp , Npy , Pmch, and Nr5a1 ( Sf1 ) were higher and Atf3 was reduced in Lep ob mice ( Allison et al., 2018 ; Elias et al., 1999 ; Elias and Purohit, 2013 ; Qu et al., 1996 ; Schwartz et al., 1996 , 1998 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of those, 562 DEGs were identified between Lep ob and WT mice ( Figure 1 C), of which 450 (80%) were upregulated and 112 (20%) were downregulated in Lep ob mice ( Figure S1 C and Table S1 ). Well-described leptin-regulated and/or energy balance-associated genes were detected: e.g., Agrp , Npy , Pmch, and Nr5a1 ( Sf1 ) were higher and Atf3 was reduced in Lep ob mice ( Allison et al., 2018 ; Elias et al., 1999 ; Elias and Purohit, 2013 ; Qu et al., 1996 ; Schwartz et al., 1996 , 1998 ).…”
Section: Resultsmentioning
confidence: 99%
“…To determine transcriptional changes in neurons directly targeted by leptin, we harvested RNA from LepRb cells by TRAP ( Heiman et al., 2014 ) and performed RNA-seq (TRAP-seq). The LepRb eGFP−L10a mice, which express a chimeric L10a ribosomal subunit fused to enhanced green fluorescent protein (eGFP-L10a), allow for eGFP immunoprecipitation of ribosomes with associated mRNAs specifically from LepRb neurons ( Allison et al., 2015 , 2018 ). This strategy enables the identification of actively transcribed mRNAs derived from PMv or Arc LepRb neurons in response to leptin administration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A proliferation modulating function has also been described for TXNIP [72] as well as for FOSL2 [73], which is also involved in leptin expression regulation [74], whereas DEPP1 downregulation has been associated with autophagy inhibition [75]. Moreover, ssc-miR-32 and ssc-miR-7-5p, two miRNAs that were differentially upregulated in AL-T1 gilts (Table 1), were predicted to target several relevant genes (Additional file 6: Table S6) such as the activating transcription factor 3 (ATF3), a key regulator of glucose and energy metabolism [76,77] which was significantly downregulated in both AL-T0/AL-T1 and AL-T0/ AL-T2 contrasts (Additional file 2: Table S2). Other relevant additional transcripts that formed part of the miRNA-to-mRNA interconnected networks were, to mention a few, the Kruppel-like factor 15 (KLF15), early growth factor 1 (EGR1) and ARID domain-containing protein 5B (ARID5B), all of which play key roles in muscle lipid metabolism [8,78,79], or myogenin (MYOG), a gene that is crucial for muscle development and differentiation [80].…”
Section: Differentially Expressed and Dispersed Mirnas Are Related Wimentioning
confidence: 99%
“…Using TRAP-seq, Allison et al [10] isolated the translating mRNA of hypothalamic LepR neurons and revealed many interesting novel markers expressed in that population. In 2018, the same team explored the response of LepR neurons to leptin treatment in wild-type and ob/ob mice and identified the transcription factor Atf3 to be upregulated by leptin [117]. In 2019, Inoue et al [7], investigated the transcriptional response of hypothalamic LepR neurons to fasting and leptin administration.…”
Section: Leptin Receptor In the Hypothalamusmentioning
confidence: 99%